Polyaniline Nano Composite for the Adsorption of Reactive Dye from Aqueous Solutions: Equilibrium and Kinetic Studies - Raffiea Baseri, J.; Palanisamy, P.N.; Sivakumar, P. (Asian Journal of Chemistry, 2013)
In the present study, polyaniline nano composite was synthesized through direct chemical polymerization. Polyaniline nano composite was tested for the removal of reactive dye, reactive orange 4 from aqueous solutions by batch adsorption technique under varying conditions of agitation time, dye concentration, pH and temperature. Lower solution pH (3 to 5) favoured the adsorption of reactive dye onto polyaniline nano composite. The dye adsorption increases from 45.83 to 143.59 mg/g on increasing the initial concentration from 25 to 100 mg/L. The pseudo second order kinetic model adequately described the kinetics of dye adsorption with high correlation coefficient (0.99). Langmuir isotherm model well fitted to the experimental data. Thermodynamic parameters like free energy (DGº), enthalpy (DHº) and entropy (DSº) were also calculated. Maximum desorption of 78.6 % for reactive orange 4 was observed at a pH range of 8 to 9. The results indicated that polyaniline nano composite is a promising adsorbent for the removal of dyes from aqueous solution.